Agricultural History Of Zamin District (2017-2024) - Dilnoza Tuychiyeva (Frontline Social Sciences and History Journal, 2025)
This article covers the state of agriculture in the Zamin region in 2017-2024, achievements and shortcomings. It also describes reforms in the sector, new projects, and the unique opportunities of the district in the export-oriented agricultural sector.